Development and characterization of cashew nut drinks (Anacardium occidentale L.) (Research, Society and Development, 2020)
The present study aimed to develop and characterize as to the physicochemical and microbiological parameters drinks based on aqueous extract of cashews and to evaluate the changes resulting from their compositions.Three formulations were made with and without added fructooligosaccharide: L1 (control drink), containing the conventional starter culture composed of Streptococcus thermophilus and Lactobacillus delbrüeckii, subsp. Bulgaricus; L2 (probiotic drink) from starter and L. acidophilus cultures; and L3 (symbiotic drink) containing starter cultures, L. acidophilus and fructooligosaccharide.The obtained products were stored at 5ºC and evaluated for the physicochemical (pH, acidity, lipids, humidity, ashes, ºbrix, syneresis and total dry extract) and microbiological variables (lactic bacteria, probiotic viability, presence of mold, yeast, total and fecal coliforms). Most of the formulations met the physicochemical and microbiological standards of Normative Instruction No. 46/2007, except for the lower than recommended acidity value and beneficial microorganism content in the L2 formulation. The symbiotic drink proved to be viable because it has adequate characteristics, proposed by the current legislation that classifies it as a functional food according to its count of viable probiotics and because it is lactose free it becomes an excellent substitute for the population that cannot consume the food. conventional dairy product. However, further studies should be performed to better characterize and adapt the products.